Simulasi Dispersi Emisi Cerobong Udara SO2, NOX, dan TSP Kegiatan Produksi Pupuk Buatan Campuran Hara Makro Menggunakan Software Aermod View - Syadzadhiya Qothrunada Zakiyayasin Nisa’; Nurabhinaya Irsyadi (Prosiding ESEC, 2023)
The fertilizer industries in East Java Province has increased in scale of production, area and human resources in line with the increase in fertilizer demand in Indonesia by 5.67%. It causes increased emissions into the atmosphere which will affect health and the environment. Therefore, an air dispersion simulation was carried out to determine the maximum level of emissions released. This study uses a modeling approach with Aermod View software to simulate the process of dispersion of CO2, NOX, and TSP air emissions in the distribution of emissions. The results of the dispersion distribution model for SO2, NOX, and TSP emissions are at a distance of 500 - 600 m from the emission source. The dispersion simulation results of the SO2 show the highest concentration of 7.34 µg/m3. The dispersion simulation results of the NOX show the highest concentration of 9.791 µg/m3. Also, the results of the TSP show the highest concentration of 1.22 µg/m3. Based on Republic of Indonesia Government Regulation no. 22/2021 Appendix VII concerning Ambient Air Quality Standards for the SO2 of 150 µg/m3, the NOX of 200 µg/m3, and the TSP of 230 µg/m3, each emission parameter still meets the established emission quality standards.